Breaking down the walls: how can we integrate gated communities into the existing urban fabric through design? - Van Dyk, Wessel (My University, 2017)
Influenced by the thinking of the Garden City movement, gated and so-called lifestyle security estates have become overwhelmingly popular in many cities across the world. With demand fuelled by a combination of security concerns and a belief that such schemes provides enhanced efficiency and comfortability, these estates have come under severe scrutiny with regards to its apparent spatial and socio-economic impacts on the city structure as a whole. However, despite the severe criticism and awareness, these types of developments have showed very little signs of decline - thus perhaps illustrating a real economic rationale in the desire of people to reside in environments with higher perceptions of safety and control. Cities respond to this by clearly delineating urban development boundaries and even in some cases publish design principles that promote integration and inclusion. These more than often become contested by means of political- and private sector influences resulting in the perpetual realities of estate development and no real prohibiting actions and remedial recourse. Given these realities, what then does the future hold for our city landscape? Could we possibly reposition ourselves now to better the outcome later? Using Steyn City and Dainfern in the Fourways area, as two mega development case studies, this academic inquiry seeks to reflect on the status quo of estate developments and creatively find internal possible clues within the very structuring elements of such schemes that could potentially unlock and ‘un-gate’ developments and in the process improve access to opportunities in the city. This could surely not only provide new insights as to what the potential future can be, but it also provides the opportunity to redefine the ‘right to the city’ and opportunity in already deprived and isolated localities.
Thesis is submitted in partial fulfilment for the degree of Master of Urban Design to the Faculty of Engineering and the Built Environment, at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--South Africa; Urbanization--South Africa; Housing--South Africa; Gated communities